Esports Games in Elementary School: A Systematic Literature Review - Hamidulloh Ibda; Muhammad Fadloli Al Hakim; Khamim Saifuddin; Ziaul Khaq; Ahmad Sunoko (Society of Visual Informatics, 2023)
Several studies have explored esports games, and few have examined esports games in elementary schools with a systematic literature review. This research explores articles on the concept, features, training, implementation, and impact of esports games in elementary schools. The SLR and PRISMA methods were applied in this research with the stages of identification, screening, eligibility, and inclusion assisted by the Publish or Perish 7, VOS viewer, and NVIVO 12 Plus applications. There were 521 Scopus-indexed articles found. Furthermore, the articles were filtered according to the theme into 50 pieces. The findings of relevant topics are esports, esports games, the concept of esports games, elementary school, etc. The 50 articles were analyzed according to the specified topics through the NVIVO 12 Plus application, and the results were described. The findings of this study state that esports games are digital innovations in online video competitions, such as tournaments developing in education. The features of esports games in elementary school are manual sports integrated with digital augmentation, multiplayer and competitive, digitalization of physical sports, new digital-based features, and educational games, such as LoL (MOBA), Battle Royal, FIFA EA Sports, Mobile Legend, WISE game, and others. Training esports games through socialization, education, workshops, GDLC, curriculum development, and multimedia esports games. Implementation of esports games through competition, entertainment, game-based multimedia, SE, and TGfU, has positive and negative impacts. This research has limitations in that it only collects information from current literature, reviews esports at the elementary school level, and is not a field study. Future research needs to examine esports games according to the times in elementary school.